Effect of BaZr0.4Ti0.6O3 addition on electrical and magnetic properties of multiferroic (1-x)BiFeO3-xBaTiO3 ceramics. (3rd October 2018) - Unruan, S.; Yimnirun, R.; Unruan, M.; Tipakontitikul, R.
Abstract: The composite 0.75(1-x)BiFeO3 -xBaTiO3 -0.25BaZr0.4 Ti0.6 O3 or 0.75(BFO-BTO)-0.25BZT ceramics (x = 0.23–0.27) have been prepared by solid state reaction method to studied the relationship between phase formation, dielectric and magnetic properties. The results found that the phase formations of calcined BFO-BTO and BZT powders are distorted rhombohedral and cubic structure, respectively. Moreover, the addition of BZT in BFO-BTO-BZT ceramics affected to the phase change dramatically according to increasing of BZT content compared to calcined BFO-BTO powders. All the samples showed cubic perovskite structure. The room temperature dielectric properties decreased with increasing of BTO content, the highest dielectric constant with low losses observed in 0.75(0.77BFO-0.23BTO)-0.25BZT ceramic. Furthermore, the ceramics displayed maximum dielectric constant temperature ( Tm ) above 360 °C. Interestingly, all ceramic compositions exhibited typical ferromagnetic hysteresis loop and the highest remanent magnetization observed in 0.75(0.77BFO-0.23BTO)-0.25BZT ceramic.